Chromosome-level genome assembly and annotation of Zicaitai (Brassica rapa var. purpuraria) - Hailong Ren; Donglin Xu; Wanyu Xiao; Xianyu Zhou; Guangguang Li; Jiwen Zou; Hua Zhang; Zhibin Zhang; Jing Zhang; Yansong Zheng (Scientific Data, 2023)
Abstract Zicaitai is a seasonal vegetable known for its high anthocyanin content in both stalks and leaves, yet its reference genome has not been published to date. Here, we generated the first chromosome-level genome assembly of Zicaitai using a combination of PacBio long-reads, Illumina short-reads, and Hi-C sequencing techniques. The final genome length is 474.12 Mb with a scaffold N50 length of 43.82 Mb, a BUSCO score of 99.30% and the LAI score of 10.14. Repetitive elements accounted for 60.89% (288.72 Mb) of the genome, and Hi-C data enabled the allocation of 430.87 Mb of genome sequences to ten pseudochromosomes. A total of 42,051 protein-coding genes were successfully predicted using multiple methods, of which 99.74% were functionally annotated. Notably, comparing the genome of Zicaitai with seven other species in the Cruciferae family revealed strong conservation in terms of gene numbers and structures. Overall, the high-quality genome assembly provides a critical resource for studying the genetic basis of important agronomic traits in Zicaitai.